GHG Emission Volume, Carbon Disclosure Quality on Firm Value: The Moderating Role of Institutional Ownership - Agis Panca Wati; Hanifah Hanifah; Muhamad Wahid Murniawan (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
Growing global greenhouse gas emissions are exerting more pressure on companies to demonstrate responsibility regarding climate issues. This research examines the effect of GHG emission volume and carbon disclosure quality on firm value among energy companies listed on the Indonesia Stock Exchange during 2020-2024, with institutional ownership as a moderating variable. Using panel data from 65 firm-year observations across 13 purposively selected companies, GHG emissions volume, carbon disclosure quality, firm value, and institutional ownership were measured and analyzed using Moderated Regression Analysis with a Fixed Effects Model. Results show that GHG Emission Volume has a negative but statistically insignificant effect on firm value, whereas carbon disclosure quality has a positive and marginally significant effect in the moderated model. Institutional ownership exerts a positive and significant direct effect on firm value, yet fails to significantly moderate either the GHG emission volume-firm value or the carbon disclosure quality-firm value relationship. These findings imply that energy companies should prioritize carbon risk management alongside governance improvements, while regulators should incentivize higher-quality carbon reporting to enhance the value relevance of GRI-305 disclosures for domestic institutional investors. A robustness check using Tobin’s Q confirms the consistency of the institutional ownership effect across alternative proxies for firm value.